2017
DOI: 10.1080/10926771.2017.1372541
|View full text |Cite
|
Sign up to set email alerts
|

Troubled or Traumatized Youth? The Relations Between Psychopathy, Violence Exposure, Posttraumatic Stress Disorder, and Antisocial Behavior Among Juvenile Offenders

Abstract: The current study examined how psychopathy, exposure to violence, and posttraumatic stress disorder (PTSD) are associated with antisocial behavior among 1,354 serious delinquent adolescents from the Pathways to Desistance study. Results showed that psychopathy, violence exposure, and PTSD are independently linked to self-reported involvement of delinquency, even after controlling for respondents’ demographic characteristics. However, the effect of PTSD on antisocial behavior was small. Differential association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
2
6
0
1
Order By: Relevance
“…The current study found that all four PTSD symptom clusters were positively correlated with antisocial behavior, consistent with previous studies, and confirms that PTSD is a risk factor for antisocial behavior (Becker & Kerig, ; Taft et al, ; Tsang, ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The current study found that all four PTSD symptom clusters were positively correlated with antisocial behavior, consistent with previous studies, and confirms that PTSD is a risk factor for antisocial behavior (Becker & Kerig, ; Taft et al, ; Tsang, ).…”
Section: Discussionsupporting
confidence: 92%
“…According to the social information processing modal of aggressive behavior (Holtzworth‐Munroe, ), the cognitive biases and unreasonable beliefs of individuals with strong symptoms of PTSD (i.e., full of threats and hostility toward their environment) are the primary causes of their aggressive behaviors among trauma survivors (Taft, Creech, & Kachadourian, ). A typical negative perception of people with PTSD is the inability to recognize that their traumatic event was a transient event that occurred in specific circumstances; rather, they generalize their feelings of loss of control and insecurity associated with the event into everyday life, which can lead to increased antisocial behavior (Tsang, ; Zhou & Wu, ).…”
Section: Ptsd Affects Antisocial Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Por otro lado, un hecho llamativo emerge al contrastar los resultados de esta dimensión con los estudios internacionales, debido a que las tasas de victimización encontradas en ambos grupos tienden a ser superiores a las reportadas en investigaciones realizadas en España, Estados Unidos y Canadá (Benedicto et al, 2017;Fanniff & Kolko, 2012;Leroux et al, 2016). De este modo, se refuerza la evidencia que indica una estrecha relación entre experiencias de esta naturaleza y posibles problemas de comportamiento sexual en edades posteriores (Barra et al, 2017;Boonmann et al, 2016;Dillard & Beaujolais, 2019;Malvaso et al, 2020;Tsang, 2017;Yoder & Precht, 2020).…”
Section: Discussionunclassified
“…The development of more reliable measures to assess psychopathic traits in young people has shown that these same traits tend to be more present in individuals with chronic criminal trajectories (McCuish, Corrado, Lussier, & Hart, 2014;Tsang, 2018), as well as other risk factors (Chauhan et al, 2014). In addition, cognitive mediating aspects between scoring and future violent behavior also need to be better understood Kahn, Ermer, Salovey, & Kiehl, 2016;Walters & DeLisi, 2015).…”
Section: Introductionmentioning
confidence: 99%